Structural insights into IL-6 signaling inhibition by therapeutic antibodies - Mingxing Wang; Long Chen; Jin He; Wenqiang Xia; Zihong Ye; Ji She (Cell Reports, 2024)
Summary: Antibody inhibitors of the interleukin-6 (IL-6) signaling pathway, such as tocilizumab and sarilumab, have been used to treat rheumatoid arthritis, chimeric antigen receptor T cell-induced cytokine storm, and severe COVID-19 pneumonia. Here, we solve the cryogenic electron microscopy structures of sarilumab and tocilizumab in complex with IL-6R to resolutions of 3.2 and 3.3 Å, respectively. These structures reveal that both tocilizumab and sarilumab bind to the D3 domain of IL-6R. The binding surfaces of the two antibodies largely overlap, but the detailed interactions are different. Functional studies of various mutants show results consistent with our structural analysis of the antibodies and IL-6R interactions. Structural comparisons with the IL-6/IL-6R/gp130 complex indicate that sarilumab and tocilizumab probably inhibit IL-6/IL-6R signaling by competing for the IL-6 binding site. In summary, this work reveals the antibody-blocking mechanism of the IL-6 signaling pathway and paves the way for future antibody discovery.